2012
DOI: 10.1111/j.1365-2966.2012.21696.x
|View full text |Cite
|
Sign up to set email alerts
|

The heating of dust by old stellar populations in the bulge of M31

Abstract: We use new Herschel multiband imaging of the Andromeda galaxy to analyse how dust heating occurs in the central regions of galaxy spheroids that are essentially devoid of young stars. We construct a dust temperature map of M31 through fitting modified blackbodies to the Herschel data, and find that the temperature within 2 kpc rises strongly from the mean value in the disc of 17 ± 1 to ∼35 K at the centre. Ultraviolet (UV) to near-infrared (IR) imaging of the central few kpc shows directly the absence of young… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
130
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(154 citation statements)
references
References 65 publications
(154 reference statements)
20
130
2
2
Order By: Relevance
“…8), such that the temperature increases with radius and β decreases. This may be linked to the β − T degeneracy because the dust temperature decreases with radius in M 31, as shown by Fritz et al (2012) using the same data, which was also reported in other studies (Groves et al 2012;Tabatabaei & Berkhuijsen 2010). It is known that the dust temperature decreases with radius in M 33 due to the radial decrease in the interstellar radiation field at all wavelengths (Verley et al 2009;Kramer et al 2010;Braine et al 2010;Boquien et al 2011;Xilouris et al 2012).…”
Section: One Of the Most Important Results Of This Work Is That We CLsupporting
confidence: 64%
“…8), such that the temperature increases with radius and β decreases. This may be linked to the β − T degeneracy because the dust temperature decreases with radius in M 31, as shown by Fritz et al (2012) using the same data, which was also reported in other studies (Groves et al 2012;Tabatabaei & Berkhuijsen 2010). It is known that the dust temperature decreases with radius in M 33 due to the radial decrease in the interstellar radiation field at all wavelengths (Verley et al 2009;Kramer et al 2010;Braine et al 2010;Boquien et al 2011;Xilouris et al 2012).…”
Section: One Of the Most Important Results Of This Work Is That We CLsupporting
confidence: 64%
“…Boquien et al (2011), Bendo et al (2012, Groves et al (2012), and Smith et al (2012b) all show that it is even possible for dust to be heated by evolved stars in a large bulge even if the dust and stars have different distributions (as is the case in M31 and M81) and that the temperature of the cold dust is tightly driven by the evolved stellar populations. Mathews et al (2013) suggest that this lack of dependency is due to the relocation of variable masses of cold dust away from the central reservoir, eventually triggered by the central AGN and then destroyed by sputtering (see also Smith et al 2012a;di Serego Alighieri et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…An additional mechanism linking the stellar mass to the dust seen at submm wavelengths is the heating by the interstellar radiation field from the total stellar population (including evolved stars), which is primarily seen at NIR wavelengths (e.g. Bendo et al 2010Bendo et al , 2012Boquien et al 2011;Groves et al 2012;Smith et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…From optical emission lines Jacoby et al (1985) estimated an ionized gas mass on the order of 1500 M , which can be accounted for by mass loss from evolving stars. Groves et al (2012) relied on Herschel data to argue that the dust properties are well accounted for by the stellar heating. Small amounts of molecular gas have been detected in directions more than 300 pc from the center.…”
Section: Introductionmentioning
confidence: 99%